2017
DOI: 10.3389/fmicb.2017.01064
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Phenotypic Detection of Microbial Resistance in Gram-Positive Bacteria by a Real-Time Laser Scattering Method†

Abstract: We developed a methodology for antimicrobial susceptibility testing (AST) based on the BacterioScanTM216R laser scattering technology, using methicillin resistance in Staphylococcus aureus and vancomycin resistance in enterococci as exemplar for important resistance phenotypes. Fifty methicillin-resistant (MRSA) and 50 methicillin-susceptible (MSSA) S. aureus, as well as 50 vancomycin-resistant enterococci (VRE) and 50 vancomycin-susceptible enterococci (VSE) isolates were used for the study. Optimal test cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Recently, it was shown that sur face labelling of bacteria substantially shortened the microscopic analysis of AST results in 96well formats using only a standard microplate reader 42 . To improve the current systems, various prototype AST methods with different approaches have been reported, includ ing the use of mobile phones 37 , laser scatter technol ogy 43 , sensing of bacterial vibrations using phase noise measurements on resonant piezo electric substrates 44 , protein adsorbed magnetic nanoparticle mediated proto cols 45 , field effect enzymatic detection 46 , microfluid ics [47][48][49] , glucose metabolization 50 , optical screening and diffusometry 51 , nanometre scale bacterial deformation measurement 52 , mass spectrometry 53 , nanowire sen sors 54 , electrochemical sensing 55 , real time laser scatter ing 56 , atomic force microscopy 57 , fluorescence activated cell sorting (FACS) 58 , Raman and infrared spectroscopy at the single cell level 59,60 , nanotube assisted micro wave electroporation 61 , hydrodynamic trapping 62 and video microscopy 63 . In this Review, we do not describe these methods in detail, due to the vast differences in the protocols.…”
Section: Zone Of Inhibitionmentioning
confidence: 99%
“…Recently, it was shown that sur face labelling of bacteria substantially shortened the microscopic analysis of AST results in 96well formats using only a standard microplate reader 42 . To improve the current systems, various prototype AST methods with different approaches have been reported, includ ing the use of mobile phones 37 , laser scatter technol ogy 43 , sensing of bacterial vibrations using phase noise measurements on resonant piezo electric substrates 44 , protein adsorbed magnetic nanoparticle mediated proto cols 45 , field effect enzymatic detection 46 , microfluid ics [47][48][49] , glucose metabolization 50 , optical screening and diffusometry 51 , nanometre scale bacterial deformation measurement 52 , mass spectrometry 53 , nanowire sen sors 54 , electrochemical sensing 55 , real time laser scatter ing 56 , atomic force microscopy 57 , fluorescence activated cell sorting (FACS) 58 , Raman and infrared spectroscopy at the single cell level 59,60 , nanotube assisted micro wave electroporation 61 , hydrodynamic trapping 62 and video microscopy 63 . In this Review, we do not describe these methods in detail, due to the vast differences in the protocols.…”
Section: Zone Of Inhibitionmentioning
confidence: 99%
“…The most basic method of detecting bacteria growth is by absorbance measurements as a function of optical density. Recent studies have employed a commercially available Forward Laser Light Scatter System (BacterioScan), which is a sensitive optical method for measuring light scattered by bacteria suspended in a liquid sample. By measuring laser light scattered at specific angles, information such as cell shape and size can be included with the density of the bacterial suspension to confirm antibiotic susceptibility with higher sensitivity than typical optical density (transmittance) measurements . Others have improved popular fluorescence sensing modalities into microarray systems capable of scanning thousands of microscopic biofilms in one readout .…”
mentioning
confidence: 99%
“…Recently, this method was applied to artificial BC pellets inoculated with Escherichia coli and resulted in complete AST in <3 h [78]. Flow cytometry performed on positive BC produced AST results in 2 h with a 98% agreement with the reference microdilution [79], while the Real-Time Laser Scattering Method correctly detected methicillin resistance in S. aureus and vancomycin resistance in enterococci in <3 h [80]. Finally, a direct-on-target microdroplet growth assay coupled with MALDI-TOF MS accurately detected antimicrobial resistance in 5 h [81].…”
Section: Innovative Technologiesmentioning
confidence: 98%